2019
DOI: 10.1002/psp4.12457
|View full text |Cite
|
Sign up to set email alerts
|

Expanded Physiologically‐Based Pharmacokinetic Model of Rifampicin for Predicting Interactions With Drugs and an Endogenous Biomarker via Complex Mechanisms Including Organic Anion Transporting Polypeptide 1B Induction

Abstract: As rifampicin can cause the induction and inhibition of multiple metabolizing enzymes and transporters, it has been challenging to accurately predict the complex drug–drug interactions (DDIs). We previously constructed a physiologically‐based pharmacokinetic (PBPK) model of rifampicin accounting for the components for the induction of cytochrome P450 (CYP) 3A/CYP2C9 and the inhibition of organic anion transporting polypeptide 1B (OATP1B). This study aimed to expand and verify the PBPK model for rifampicin by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(61 citation statements)
references
References 41 publications
1
60
0
Order By: Relevance
“…22 In fact, CP-I was used for OATP1B activity phenotyping in clinical drug-drug interaction studies 24,[37][38][39] and in model-based analysis of drug-drug interactions. 23,[40][41][42] Three previous studies reported the relationship between plasma CP-I concentrations and OATP1B1 polymorphism, but the numbers of participants in all studies were insufficient to detect significant differences among the genotypes. 25,27,28 In the present study of a large sample from the Japanese Hepatic failure decreased mRNA levels of OATPs in liver biopsy specimens in a previous study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 In fact, CP-I was used for OATP1B activity phenotyping in clinical drug-drug interaction studies 24,[37][38][39] and in model-based analysis of drug-drug interactions. 23,[40][41][42] Three previous studies reported the relationship between plasma CP-I concentrations and OATP1B1 polymorphism, but the numbers of participants in all studies were insufficient to detect significant differences among the genotypes. 25,27,28 In the present study of a large sample from the Japanese Hepatic failure decreased mRNA levels of OATPs in liver biopsy specimens in a previous study.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, CP‐I is assumed to be the most sensitive and specific biomarker for phenotyping of OATP1B activity compared with the other endogenous biomarkers and probe drugs, such as HMG‐CoA reductase inhibitors 22 . In fact, CP‐I was used for OATP1B activity phenotyping in clinical drug‐drug interaction studies 24,37–39 and in model‐based analysis of drug‐drug interactions 23,40–42 . Three previous studies reported the relationship between plasma CP‐I concentrations and OATP1B1 polymorphism, but the numbers of participants in all studies were insufficient to detect significant differences among the genotypes 25,27,28 .…”
Section: Discussionmentioning
confidence: 99%
“…Incorporation of OATP1B induction into PBPK models for the OATP1B substrates glibenclamide, repaglinide, and coproporphyrin I more accurately described the clinically observed interactions following multiple-dose rifampin administration than models incorporating only CYP induction and OATP1B inhibition. 21 Nonetheless, improved PBPK model fit can only support a hypothesis, but does not provide unequivocal mechanistic proof of a DDI mechanism.…”
Section: Hepatic Oatp1bmentioning
confidence: 99%
“…For the perpetrator PBPK model, it is crucial to correctly predict the unbound concentrations at the site of the drug interaction (e.g., intestine, liver, or kidneys) and provide accurate estimates of the interaction parameters (e.g., K i , E max ). The above aspects are of key importance to simultaneously evaluate multiple inhibitions and induction mechanisms and to accurately predict the potential of DDIs [ 81 , 82 ].…”
Section: Dynamic Pbpk Model For Pk Ddismentioning
confidence: 99%
“…For enzyme-based metabolism, Equation (18) shows the CL μ,int of the victim drug in the absence of the perpetrator, and Equation (19) indicates the dynamic changes of the CL μ,int of the victim drug in the presence of the perpetrator. Regarding the transporter-mediated elimination, the impact of the perpetrator on the PS uptake and/or PS efflux of the victim drug can be determined in a similar way as CL μ,int [ 82 ]. If intestine clearance can be ignored and CL μ,int,h in the liver is known, CL μ,int , PS uptake , and PS efflux can be obtained from Equation (11) (“extended clearance concept”) via back-calculation.…”
Section: Dynamic Pbpk Model For Pk Ddismentioning
confidence: 99%